The Effect of the Inquiry Learning Model Assisted by PhET Digital Simulation Media on the Learning Outcomes of Grade IV Science: Pengaruh Inquiry Learning Model Berbantuan Media Simulasi digital PhET Terhadap Hasil Belajar IPAS Kelas IV - Azila Wana Fridestu; Ahmad Ilham Asmaryadi; Wiwik Okta Susilawati (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
The low student achievement in the IPAS subject highlights the need to implement innovative learning strategies that can enhance students’ active engagement in the learning process. One approach that can be taken is to implement a discovery-based learning model combined with the use of the PhET Simulation digital platform. This study aims to determine the effect of implementing an inquiry-based learning model supported by the PhET Simulation platform on the IPAS learning outcomes of fourth-grade students at SDN 12 Koto Baru. This study employed a quantitative approach using a pre-experimental method with a single-group pretest-posttest design. The study subjects consisted of 22 fourth-grade students. Research data were collected through learning outcome tests in the form of pretests and posttests. Data analysis was conducted using the Shapiro-Wilk normality test and the paired-sample t-test. The results showed an improvement in students’ learning outcomes following the implementation of this learning model. This was evident from the increase in the students’ average score, which rose from 54.04 in the pretest phase to 89.45 in the posttest phase. The hypothesis test yielded a significance value of 0.000 (<0.05), indicating that the implementation of the inquiry-based learning model supported by PhET digital simulations had a significant effect on the IPAS learning outcomes of fourth-grade students at SDN 12 Koto Baru.